The role of the Notch signaling pathway in rhabdomyosarcomas - Datis Kalali; Emilija Milošević; Doxakis Anestakis; Doxakis Anestakis (European Journal of Translational and Clinical Medicine)
Rhabdomyosarcoma (RMS) is a pediatric soft tissue cancer with poor prognosis in cases of metastasis. Different signal transduction pathways have been studied in RMS cells as to shed some light into the tumorigenesis and metastasis mechanisms of this cancer in the search for new diagnostic and therapeutic strategies. The Notch pathway, which regulates cell survival, is widely studied in different cancers, including sarcomas and its activation has been known to induce cell motility. To this end, the present review explores the role of the Notch signaling pathway in the progression of RMS and in potential therapeutic strategies.